Contemporary techniques of graphic art and its representations - Rana Hazim Saeed (Basrah Arts Journal, 2023)
The research tagged (Representations of Contemporary Technologies in Graphic Art) deals with the dialectical relationship between the diversifications of technologies within their temporal developments and the structure of graphic work, especially in our current era and the huge openness of digital technologies and their cultural influences in thought and their functional deliberations in life and their aesthetic representations in art. This faces a cognitive tangle and questions represented in: 1. What is the cognitive space of graphic techniques between the primitive and contemporary edges? 2. How did reproduction replace the original in contemporary circulation? The importance of the research is represented in the following points: 1. The research deals with one of the forms of arts whose historical presence has indicated through time and space. 2. The research seeks to seriously explore the roots of an artistic phenomenon seeking to innovate manifestations of the beautiful always. 3. The research monitors and analyzes the phenomenon of archaeological transition from immanent to transcendental. The boundaries of the research receded between the early days of the spread of digital technologies in the visual arts, including graphics, and the researcher chose the year 1970 to the year 2023 to contain the research problem from its beginnings to its conclusions. Therefore, to the basic indicators reported in the third chapter, which dealt with three distinct models as a research sample, and concluded from its analysis to the results of the research that were discussed in the fourth chapter, and the researcher drew conclusions from them and identified recommendations and proposals.